Pengujian Kandungan Unsur Hara Pupuk Organik Cair (POC) Limbah Kulit Nenas - Neng Susi; Surtinah Surtinah; Muhamad Rizal (Jurnal Ilmiah Pertanian, 2018)
This research was conducted at the Laboratory of Faculty of Agriculture, University of Lancang Kuning. The study was conducted for 3 months from September to November 2015. This study is a descriptive research, where the first process is the process of making organic fertilizer derived from pineapple skin waste fermented for 1 month POC that has been taken samplenya and tested in the laboratory to determine the content of micro and macro nutrients and C-organicnya. To measure macro and micro nutrient content, the test method used was Kjeldahl for nitrogen content, while for P, K, CaO, MgO and Fe, the Atomic Absobtion spectrophometric (AAS) method was used and the C-organic content was tested by spectrophometric method. The results showed that POC of Pineapple Skin Waste contained P 23,63 ppm, K 08,25 ppm, N 01,27%, Ca 27,55 ppm, Mg 137,25 ppm, Na 79,52 ppm, Na 79, 52 ppm , Fe 1,27 ppm, Mn 28,75 ppm, Cu 0,17 ppm, Zn 0,53 ppm and C Organic 3,10%.